Strategies for Enhancing the Communicative Competence for Students with Learning Disabilities - Gladday, Ataisi Emiya (Richtmann Publishing, 2011)
The essence of language teaching in Nigerian schools is to improve the communicative competence of students inEnglish Language. The frequent poor performance of students in English Language means that language teachers need toreconsider the appropriateness of the teaching methods. In view of the fact that there are students with learning disabilities inmainstream schools, this paper highlights some motivational strategies that can enhance the communicative competence ofstudents with learning disabilities. The paper explains in details these motivational strategies and the benefits. Finally, the paperconcludes by calling on language teachers to adopt an eclectic method in language teaching through the use of the pedagogicalstrategies examined. It is hoped that these motivational strategies would be adopted for corrective and remedial instruction inlanguage teaching.